Implementation of geocast-enhanced AODbis routing protocol in MANET - Ooi, Chia Ching (2005)
Mobile Ad Hoc Network (MANET) has attracted extensive research interests over the past several years. However, far less effort has been done on the real implementation of MANET. This thesis explains the development and implementation of MANET test bed based on geocast-enhanced Ad-hoc On-Demand Distance Vector-bis (AODVbis) routing protocol. The MANET test bed consists of laptops, desktops and PDAs. Each of them was equipped with wireless network cards and configured to run in ad hoc mode. Linux and Familiar OS were chosen as their operating platform due to the open-source nature, which allows free access to the OS kernel especially the network protocol stack. AODVbis is an improved design of AODV routing protocol featuring path accumulation. The AODVbis routing module has been developed by using C language and executed at kernel level. To enhance the AODVbis routing protocol, a geocast-enhancement module has been coded and integrated into AODVbis so that location information can be utilized during the route discovery based on geocast instead of broadcast. A GPSfree location tracking program was installed in each node to obtain the distance value required during route discovery. The results obtained from the verification of AODVbis module shows that the AODVbis is more powerful than AODV especially in route dissemination. With the integration of geocast-enhancement module into AODVbis, the forwarding zone is restricted during route discovery. Consequently, the number of broadcast is significantly reduced especially in a dense network. In general, the geocast-enhanced AODVbis routing protocol has been implemented and verified successfully in the MANET test bed. The experimental results have shown that the average packet delivery ratio is high (more than 90%) while both the average minimum end-to-end delay and average route reconstruction time for a 2-hop communications are reasonably low and within milliseconds.